The Influence of Transformational Leadership and Perceived Organizational Support on Employee Performance through Organizational Citizenship Behavior and Job Satisfaction - Adrian Bosrin; Ana Fitriana; Dody Pratama Marumpe; Ilzar Daud; Mazayatul Mufrihah (Al-Qalam Institue, 2026)
This study aims to examine the effects of transformational leadership and perceived organizational support on employee performance, with organizational citizenship behavior and job satisfaction as mediating variables. A quantitative approach was employed using a survey method involving 228 employees selected through accidental sampling. Data were collected using Likert-scale questionnaires and analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS) through SmartPLS 4.0. The results reveal that transformational leadership has a significant negative direct effect on employee performance, while perceived organizational support does not have a significant direct effect. However, both transformational leadership and perceived organizational support have positive and significant effects on organizational citizenship behavior and job satisfaction. Furthermore, organizational citizenship behavior and job satisfaction positively and significantly influence employee performance and serve as mediating variables. These findings indicate that improving employee performance is more effectively achieved through fostering positive work attitudes and discretionary behaviors rather than relying solely on direct leadership influence. The study highlights the importance of strengthening supportive organizational climates and enhancing employee satisfaction to sustain performance outcomes.